Solution-processable, star-shaped bipolar tetraphenylethene derivatives for the fabrication of efficient nondoped OLEDs. Issue 14 (13th November 2015) - Chen, Long; Zhang, Chongyang; Lin, Gengwei; Nie, Han; Luo, Wenwen; Zhuang, Zeyan; Ding, Siyang; Hu, Rongrong; Su, Shi-Jian; Huang, Fei; Qin, Anjun; Zhao, Zujin; et al.
Abstract : Star-shaped tetraphenylethene derivatives containing electron-donor and acceptor groups are synthesized and utilized in solution-processed nondoped OLEDs. Abstract : Organic light-emitting diodes (OLEDs) based on solution-processable small molecules are attracting intense attention, as such technology combines the merits of low-cost solution processability of polymers and finely defined structural uniformity of small molecules. Small-molecule tetraphenylethene (TPE) derivatives are excellent solid-state light emitters featuring aggregation-induced emission (AIE) characteristics, however those that can be used in solution-processable devices are very rare. To address this issue, herein, a series of novel star-shaped bipolar TPE derivatives are synthesized and characterized. Their thermal stabilities, photophysical properties, electronic structures, electrochemical behaviors, and application in solution-processed OLEDs are investigated systematically. These luminogens exhibit AIE characteristics and excellent fluorescence quantum yields up to 95% in the solid state. Nondoped OLEDs are successfully fabricated through a spin-coating method. The solution-processed OLEDs [ITO (130 nm)/PEDOT:PSS (40 nm)/emitter (70 nm)/TPBi (30 nm)/Ba (4 nm)/Al (120 nm)] adopting star-shaped TPE derivatives as light-emitting layers show peak luminance of 11 665 cd m −2 and high electroluminescence (EL) efficiencies up to 8.3 cd A −1, 2.6% and 7.5 lm W −1 . These results demonstrate a promising avenue towards efficient nondoped OLEDs based on solution-processable AIE-active small molecules.